Subconscious Learning via Games and Social Media - Sourina, Olga (Springer, 2015)
This book provides a detailed update on the applications of Serious Games in Healthcare and Education sector. In short, it provides an all rounded research and industry updates about the current and future advances in this area. These are the two sectors that are developing rapidly with direct applications of serious games. With advances in technologies and a new perspective on patient engagement and public expectations, the healthcare sector is increasingly turning to serious games to solve problems. Subconscious Learning via Games and Social Media will share expert opinions on the development and application of game technologies for health-related serious games. Our commercial and non-commercial expert comes from different aspects of the healthcare system from clinicians to therapist. The scope ranges from population health to specific medical domain applications. In the education sector, digital games have a great potential to improve learning of both adults and children. It is important to understand how to design games that could create long term behavioral change rather than short term alterations. In these chapters, we discuss how the serious games should be designed and deployed for both adults and children. Table of contents (10 chapter) A Evaluation of 3D Character Reflectance and Realistic Implementation for FPS Game